The SAGE handbook of aging, work and society / edited by John Field, Ronald J. Burke, Cary L. Cooper - Field, John; Burke, Ronald J.; Cooper, Cary L. (Los Angeles : SAGE Publications Ltd., 2013)
Key international contributors come together to create a definitive map of the subject. Framed by an authoritative introductory chapter, 'The SAGE Handbook of Aging, Work and Society' offers a critical overview of the most significant themes and topics, with discussions of current research, theoretical controversies and emerging issues